1978
DOI: 10.1007/bf02665367
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid oxidation catalyzed by various amino acids and cupric ions in freeze‐dried model systems

Abstract: The present investigation into the effect of amino acids on linoleic acid oxidation in freeze‐dried model system illustrates the existence of an autocatalytic chain reaction, in which all amino acids, except cysteine, exhibited minor antioxidant behavior. The antioxidant effect might be attributed to the absence of protonated amino nitrogen. Linoleic acid alone had an induction period of 15 hr, and on the addition of various α‐amino acids, the systems had induction periods ranging from 16‐19 hr. This increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Ascorbic acid also exhibited only a slight stabilizing action but quercetin exhibited a strong protective effect. In freeze dried emulsions containing safflower oil or linoleic acid, amino acids, except cysteine have been reported to exhibit a slight antioxidant effect (Farag et a/., 1978;Riisom, Sims & Fioniti, 1980) but in aqueous emulsions, amino acids had both pro-and anti-oxidant effects (Marcuse, 1961;Farag et al, 1978;Riisom, Sims & Fionti, 1980).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Ascorbic acid also exhibited only a slight stabilizing action but quercetin exhibited a strong protective effect. In freeze dried emulsions containing safflower oil or linoleic acid, amino acids, except cysteine have been reported to exhibit a slight antioxidant effect (Farag et a/., 1978;Riisom, Sims & Fioniti, 1980) but in aqueous emulsions, amino acids had both pro-and anti-oxidant effects (Marcuse, 1961;Farag et al, 1978;Riisom, Sims & Fionti, 1980).…”
Section: Resultsmentioning
confidence: 95%
“…It was observed that the rate of carotenoid destruction was significantly higher in blanched freeze-dried carrots than in unblanched freeze-dried carrots. However, in the conventional hot air drying process blanching is known to significantly enhance the stability of carotenoids during storage (Feinberg et al, 1964). Since in the freeze drying process, the carrots are first frozen and subsequently moisture is removed by sublimation, the effect of freezing before conventional hot-air drying on the stability of carotenoids during storage was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, metal binding ability does not imply a protection against lipid oxidation. Amino acids, for example, may exhibit pro-oxidative effects in the presence of transition metals (17)(18)(19)(20). Therefore, the effect of Cu(II) on the rate of lipid oxidation in the presence of MRP or histidine, heated or not, was evaluated by a Rancimat measurement of the induction period.…”
Section: Resultsmentioning
confidence: 99%
“…The current study suggests that a thioether may be more effective than a thiol in preventing oil oxidation at frying temperatures. The strong activity of lysine, tryptophan, and arginine containing an extra amine group was explained by radical scavenging activity of the amine group and production of antioxidant compounds by reactions of the amine group with oxidized lipids (Choe & Min, ; Farag, Osman, HallaBo, Girgis, & Nasr, ).…”
Section: Resultsmentioning
confidence: 99%